Basketball How Means Physical Education - Andrey Igorevich Platunov (Euro Asian Journal Publishing, 2025)
This article discusses that a sports game, as Basketball is a means of physical education in higher education institutions and is taught as a subject in the curriculum based on the public education system of our country.
Keywords: physical upbringing; basketball; students